Factors affecting cadmium toxicity to rice germinated in soils collected from downstream areas of abandoned zinc mines - P. Chanpiwat; A. Numprasanthai (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Cadmium contamination in rice grains with a maximum concentration 19 times the national food standard at sites downstream of zinc mines in Thailand has been reported since 2005. These cultivated rice grains are consumed by local residents and have increased the risk of renal dysfunction in residents. Decreasing negative health effects by reducing cadmium accumulation in rice should be considered. Since the soil characteristics affecting the toxicity and accumulation of cadmium in rice cultivated in cadmium-contaminated soils have never been reported, this study was conducted to investigate the soil characteristics affecting the plant availability and mobility of cadmium in paddy soils and the impacts of these soil characteristics on rice seed germination and accumulation in rice.METHODS: The study area is the Mae Tao Subdistrict, Mae Sot District, Tak Province, located downstream of abandoned zinc mines in northwestern Thailand. A total of 36 paddy fields that were reported to produce rice grain with cadmium contents exceeding the national standard for cadmium in rice (0.4 milligrams per kilogram) were randomly selected for composite soil sample collection. The physicochemical characteristics of the soils, including soil texture, redox potential, cation exchange capacity, potential of hydrogen, organic matter, total cadmium concentration, and chemical speciation and concentration of plant-available cadmium, were analyzed. The toxicity of cadmium to rice and the cadmium accumulation ability in rice were assessed through the germination of Khao Dok Mali 105, a popular rice variety for cultivation and consumption in the study area.FINDINGS: Total cadmium concentrations of 0.20 to 89.87 milligrams/kilogram were found in the soils, with 64 percent of all samples containing values greater than the national background value in agricultural soils. Up to 74.2 percent and 99.5 percent of total cadmium was found in the forms of mobile- and plant-available cadmium, respectively. Plant-available cadmium caused significant reductions in the number of seeds germinated and root length. Cadmium toxicity to rice was positively affected by the concentrations of exchangeable, plant-available and total cadmium. The concentrations of plant-available, exchangeable, carbonate-bound, and total cadmium strongly affected the accumulation of cadmium in germinated roots. Cluster analysis showed that plant-available cadmium was the main factor responsible for high cadmium accumulation in rice.CONCLUSION: Based on the overall analyses of soil characteristics affecting the mobility and plant availability of cadmium in soils and its toxicity and accumulation in germinated rice, the immobilization of plant-available cadmium in soils by adding organic matter-rich amendments to soils is recommended. In addition, oxidizing soil conditions should be maintained during rice cultivation to reduce the phytoavailability of cadmium in soils.